2023
DOI: 10.1186/s40249-023-01086-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased interleukin-6 is associated with long COVID-19: a systematic review and meta-analysis

Abstract: Background Coronavirus disease 2019 (COVID-19) can involve persistence, sequelae, and other clinical complications that last weeks to months to evolve into long COVID-19. Exploratory studies have suggested that interleukin-6 (IL-6) is related to COVID-19; however, the correlation between IL-6 and long COVID-19 is unknown. We designed a systematic review and meta-analysis to assess the relationship between IL-6 levels and long COVID-19. Methods Data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 54 publications
2
27
1
4
Order By: Relevance
“…Notably, subsegmental emboli had the lowest rate of persistence, while central emboli showed the highest rate of persistence; a higher rate of persistence of central emboli has already been described [35]. The higher level of IL-6 in patients with persistent thrombotic defects may instead be related to the persistence of symptoms in COVID-19 patients, which would be consistent with previous studies [36].…”
Section: Discussionsupporting
confidence: 88%
“…Notably, subsegmental emboli had the lowest rate of persistence, while central emboli showed the highest rate of persistence; a higher rate of persistence of central emboli has already been described [35]. The higher level of IL-6 in patients with persistent thrombotic defects may instead be related to the persistence of symptoms in COVID-19 patients, which would be consistent with previous studies [36].…”
Section: Discussionsupporting
confidence: 88%
“…Other immunological (dys) regulation processes are also suspected to influence the development of LC, e.g., Th‐17 or cytokine activity, in particular interleukin (IL) 6 53,54 . In a recent systematic review and meta‐analysis of 16 studies, Yin et al even postulate that increased IL‐6 levels might predict LC 55 …”
Section: Discussionmentioning
confidence: 99%
“…In the context of viral respiratory infections, innate immune responses activate innate lymphocytic cells of a type‐2 phenotype (ILC‐2) which release a range of cytokines associated with allergic diseases 55 . This process has been observed in COVID‐19 patients and linked with more favourable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was an observed elevation in lymphocytes and IL-6 in these patients (Yong, Halim et al 2023). Yin et al (2023) also reported a significant increase in IL-6 levels in LC patients compared to healthy controls (Yin, Agbana et al 2023).…”
Section: Introductionmentioning
confidence: 98%
“…However, the two meta-analyses that examined immune functions in LC did not provide a comprehensive examination of the immune profiles, including the neurotoxicity profile (Yin, Agbana et al 2023, Yong, Halim et al 2023). Therefore, a more extensive examination of cytokines/chemokines/growth factor profiles in LC would be instrumental in elucidating the mechanisms of this illness.…”
Section: Introductionmentioning
confidence: 99%